General aspects of Quechua deixis - Hurtado de Mendoza Santander, William (2000)
One of the most recognized characteristics of Andean linguistics is the rigor with which it has described and reconstructed the languages, however, it has ignored the cultural context and has left, practically untouched, the universes of meaning and sense, as well as the use that the actors of the culture make of those meanings. This situation has generated a vacuum in those fields that are proper to Quechua semantics, semiotics and pragmatics and that, as such, need to be approached, but not only having culture as an essential frame of reference, but also starting from it.